Associations between sociodemography and environmental factors and blood lead (PbB) level among secondary male school students in two districts in Selangor, Malaysia - Ahmad, Asilah (2014)
The risk factors of PbB levels on adolescents have not been fully described in Malaysia. Due to insufficient local data, this cross-sectional study was conducted to determine the sociodemography and environmental risk factors as well as the predictors of PbB levels among secondary male school students in two districts in Selangor. This study would provide valuable insight on the possible lead exposure routes among understudied subjects and to set basis for future studies on lead-adolescent. This study involved 194 of Form 2 and Form 4 students attending school in Petaling and Hulu Langat districts. Two-stage sampling was applied as the sampling technique, with stratification by schools and forms. At the first stage, schools were selected at random using a sampling frame containing a list of government secondary schools in the selected districts obtained from Selangor State of Education Department. At the second stage, respondents were selected based on exclusive and inclusive criteria using sampling frames containing lists of students in Form 2 and Form 4, obtained from their respective schools. Finger-prick method was applied to obtain capillary blood specimen. PbB was determined using an atomic absorption spectrometer equipped with graphite furnace. Both sociodemography characteristics (age, family structure, mother’s educational attainment, father’s educational attainment, mother’s working status, father’s working status, and family income) and environmental characteristics (household smoking, respondent smoking, type of housing, length of residence, house age, house paint, type of pipe system, distance house-major road, distance house-factory, and school location) were obtained from self-administered questionnaires. The results showed that the mean PbB concentration was 4.61μg/dL (95% CI: 4.01−5.21μg/dL). Prevalence of PbB concentration more than 10μg/dL for urban school going adolescents was 5.7%. There were significant differences in the mean of log-transformed PbB with father’s working status, family income, type of housing, and school location. Higher PbB levels were observed in respondents who had working father, family income < RM3,000, living in unstructured housing, and attending school in industrial area. This study also observed a non-significant increasing trend of PbB concentration as (1) father’s highest education decreases and as (2) respondent cigarettes intake increases. Multivariable analysis indicated that living in unstructured housing and having working father were the significant predictors for PbB levels. Null hypothesis was rejected in favour of alternative hypothesis. Socio-demographic factor namely father’s working status and environmental factor namely type of housing were predictive of PbB levels. In conclusion, the variations in PbB levels on this population were mostly due to other contributing factors outside the study scope. As the environmental factors used in this study are reflective towards assessing indoor exposure, this study suggests that lead exposure in these adolescents was largely contributed from other unknown sources, more likely to be from outdoor sources, yet to be identified.